2022
DOI: 10.1186/s13023-022-02484-6
|View full text |Cite
|
Sign up to set email alerts
|

Sanfilippo syndrome: consensus guidelines for clinical care

Abstract: Sanfilippo syndrome is a group of rare, complex, and progressive neurodegenerative lysosomal storage disorders that is characterized by childhood dementia. The clinical management of patients with progressive neurological decline and multisystem involvement requires a multidisciplinary team with experience in the management of neurodegenerative disorders. Best practice guidelines for the clinical management of patients with these types of rare disorders are critical to ensure prompt diagnosis and initiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 123 publications
(236 reference statements)
2
26
0
Order By: Relevance
“…Therefore, additional testing of our MPS III models is warranted using behavioural tests for phenotypes not due to neurodegeneration. Differences in anxiety-related behaviours are common in human patients [1,2],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional testing of our MPS III models is warranted using behavioural tests for phenotypes not due to neurodegeneration. Differences in anxiety-related behaviours are common in human patients [1,2],…”
Section: Discussionmentioning
confidence: 99%
“…MPS III presents enormous challenges to the families of affected children due to the broad range of cognitive and behavioural changes accompanying the disease. The disease course begins with failure to achieve developmental milestones, followed by onset of behavioural symptoms such as hyperactivity, aggression and sleep disturbances [1][2][3]. Later stages of the disease involve progressive loss of cognition, speech, mobility and, eventually, deterioration of autonomic bodily functions such as swallowing and respiration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with mucopolysaccharidoses often have ocular manifestations such as retinopathy, optic nerve abnormalities, corneal clouding, and glaucoma (Ashworth et al, 2006; Fahnehjelm et al, 2012; Ferrari et al, 2011). In MPS IIIA, the most frequent ocular feature is a progressive retinopathy (Muschol et al, 2022; Wilkin et al, 2016), that is also found in all patients with late‐onset forms (Nijmeijer et al, 2019), suggesting that retinal homeostasis is particularly sensitive to SGSH deficiency. Photoreceptor dysfunction was indeed an early sign of neuronal symptoms also in a mouse model of MPS IIIA (Intartaglia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The American Diabetes Association lists Standards of Medical Care in Diabetes specific to pediatrics including "At diagnosis and during routine follow-up care, assess psychosocial issues and family stresses that could impact diabetes management and provide appropriate referrals to trained mental health providers, preferably experienced in childhood diabetes." Members of Cure Sanfilippo Foundation (USA) and Sanfilippo Children's Foundation (Australia) formed a steering meeting to determine Standards of Care for Sanfilippo Syndrome and stated "proactive intermittent assessment of caregivers' anxiety, depression, and chronic traumatic stress with appropriate referral is warranted" (Muschol et al, 2022). Taken together, these examples each highlight the possibility to develop standards affirming the necessity of addressing the mental health of parent caregivers across a wide range of pediatric health conditions.…”
Section: Existing Caregiver-oriented Standards Of Care In Pediatric S...mentioning
confidence: 99%